Where are we with respect to research in support of sustainable development goal 13? bibliometric analysis - Fernandez Zarate, Franklin Hitler; Pérez Delgado, Luis; Coronel Bustamante, David; Huanca Silva, Leisy; Taboada Mitma, Victor H.; Quispe Carhuapoma, Mariela; Oliva Alvarez, Yashira; Huaccha Castillo, Annick Estefany; Seminario Cunya, Alejandro; Quiñones Huatangari, Lenin; Ocaña Zuñiga, Candy Lisbeth; Morales Rojas, Eli; et al. (International Information and Engineering Technology Association (IIETA), 2025)
Climate change is one of the main global challenges, addressed in the United Nations Sustainable Development Goal (SDG) 13, which seeks to "take urgent action to combat climate change and its impacts". The objective of the research was to analyze scientific articles that directly relate to SDG 13 through a bibliometric analysis for the period 2015 to 2024 of the Scopus database using the search term “SDG 13” OR “Sustainable Development Goal 13”. The research identified prolific authors, articles, sources with the highest impact in the area of study, leading institutions and countries in publications along with a detailed keyword analysis. The results show that interest in the study of SDG 13 has grown significantly with a focus on areas such as mitigation and adaptation, low carbon economy and public policy. This analysis provides an overview of advances in SDG 13 research, helps to identify knowledge gaps and emerging areas, and contributes to the formulation of effective policies and the drive for global climate action.